Analysis of Breakfast Attributes and Utility Among Indian Urban Youth - Tomar, Vivek Singh (Indian Journal of Marketing, 2017)
Across various cultures and nationalities, most of us break our fast with the first meal of the day called breakfast. For players in the food industry like restaurants, chain of food kiosks, fast food outlets, and packaged food manufacturing companies engaged in marketing ready to cook, ready to eat, heat and eat kind of products, breakfast is a huge consumer market. The present study aimed at analyzing breakfast attributes and its utility among Indian urban youth ; the attributes like preferred breakfast time, calorie intake of breakfast, and preferred mode of consumption of breakfast which determined the perception and utility of breakfast among the target population. Other attributes associated with breakfast like health, nutrition, filling/ satiation, hygiene, taste, economy, and convenience were also analyzed in detail. Data were collected from 328 urban youth in the age group of 18-22 years across five major cities of India. Descriptive analysis, difference analysis using independent sample t - test, one way ANOVA, and multivariate conjoint analysis were used to reveal the consumer preferences on various breakfast attributes.